Cerebral Radionecrosis in Patients with Nasopharyngeal Carcinoma - Ying-Che Hsu; Ling-Feng Wang; Ka-Wo Lee; Kuen-Yao Ho; Wen-Rei Kuo (Kaohsiung Journal of Medical Sciences, 2005)
This study involved seven patients with cerebral radionecrosis following radiation therapy for nasopharyngeal carcinoma (NPC). Their charts were reviewed and the relationship of extracranial malignancies to cerebral radionecrosis was investigated. The radiation dose ranged from 70 to 135 Gy, and the latency was from 6 to 39 months. Two of seven patients died of NPC-related complications during follow-up. The crude incidence of cerebral radionecrosis in patients with NPC was 0.93% in our series. Improvement of symptoms could be achieved by corticosteroid therapy, with or without surgery. In a review of the literature, there were 306 cases of cerebral radionecrosis in extracranial malignancies. The nasopharynx is the most common primary site in cerebral radionecrosis of extracranial malignancies, followed by the scalp and sinonasal tract. The 3-year overall survival rate in our series was 68.57%, as provided by the Kaplan-Meier product limited method. Cerebral radionecrosis in NPC patients should be differentiated from tumor recurrence, in order to apply the appropriate treatment.